Future Educators in a Technological Society (Docentes 2.0 Journal, 2024)
The healthy use of technology has become essential in today's society. Teaching and student skills play a crucial role in correctly implementing technology. The objective was to know the level of knowledge and use of technology: students, parents, and teachers. The research was based on the inductive method, with a quantitative approach, experimental, descriptive, and cross-sectional design. Three Primary Education schools and one Secondary Education institute participated in the study. Questionnaires were passed and previously validated by a group of experts. Permission was requested from the Educational Inspection and the JCCM Education Department to pass them on. We worked with three programs for data coding: Excel, Statgraphics 19, and SPSS. The need for training and information was noted to maximize the benefits and minimize the possible negative impacts of misuse of technology. As parents, educators, and community members, we must promote balanced and responsible use of technology to ensure a safe and healthy digital environment. It is necessary to educate, raise awareness, and generate a critical spirit in the student (in the case of teachers) and the child (their parents) who are beginning to use technology to generate responsibility in creating secure and unique passwords for each account.
Keywords: Technology; security; training and information